Innovative Logistics Service Capability: Its Impact on Competitiveness and Performance - Sudrajat, Darjat -; Budiastuti, Dyah; Kuncoro, Engkos Achmad; Setiadi, Nugroho Juli (International Journal of Supply Chain Management, 2020)
Nowadays, Nowadays, Indonesian Logistics Service Providers (LSP) need to improve their performance to enable them competing with foreign logistics service providers with particular reference to cope with the ASEAN Economic Community (AEC). The main purpose of this research is to investigate the impact of innovative logistics service capability (INOV) on LSPâ€™s performance (PERFORM) and competitiveness (COMP). The research model was developed based on previous theories and researches. This research constituted a causal research. It used questioners in collecting data from respondents by applying probability sampling with sample size consist of 280 logistics service providers (LSP) in Jakarta (Jabodetabek Region). The model was examined through structural equation modeling (LISREL). In the research was also conducted investigation about role of LSPâ€™s competitiveness (COMP) in mediating the effect of innovative logistics service capability (INOV) on firm performance (PERFORM).Â